THE ROLE OF REHABILITATION IN PRIMARY CARE - Laziz.N. Tuychiev; Umid E. Eraliev; Gulnara.K. Khudaykulova; Nilufar K. Djuraeva (Scholar Express Journals, 2022)
The article reveals a fact that still worries the population of the whole world and is relevant is the prevention of early and late complications of COVID-19 in those who have experienced it. Taking into account the importance of the activities of the primary division of medicine in ensuring the continuity of the same process, their activities were studied and analyzed, as a result of which rehabilitation measures are carried out in patients with the disease, and at subsequent stages, as a result of integrity violations, patients return to normal life. The autonomy of patients with COVID-19 infection before rehabilitation was also studied, divided into groups, and the role of doctors and medical staff in ensuring that they receive the necessary treatment and undergo rehabilitation is envisaged
Keywords: COVID-19; treatment and rehabilitation; prevention; quarantine